2017
DOI: 10.1007/s11010-017-3123-9
|View full text |Cite|
|
Sign up to set email alerts
|

ACE2, CALM3 and TNNI3K polymorphisms as potential disease modifiers in hypertrophic and dilated cardiomyopathies

Abstract: The marked clinical and genetic heterogeneity seen in hypertrophic (HCM) and dilated cardiomyopathies (DCM) suggests involvement of disease modifiers and environmental factors in the pathophysiology of these diseases. In the current study, we examined association of single nucleotide polymorphisms (SNPs) of three candidate genes, ACE2 (rs6632677), TNNI3K (rs49812611) and CALM3 (rs13477425) with clinical phenotypes of HCM and DCM patients of North Indian ethnicity. Prevalence of ACE2 (7160726 C>G) variant genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
0
13
1
1
Order By: Relevance
“…In the Framingham Heart Study [41], every 5-mm increase in LAD increased the development of AF by 39%. A recent study correlated rs6632677 with left ventricular remodeling [42], and it has been associated with AF risk in the Chinese population [43]. In contrast, we found that rs6632677 was not associated with risk of AF (see Supplementary Table 7), and the genotypes of the 3 ACE2 SNPs associated with LAE were also associated with increased AF risk (OR = 2.20–2.62).…”
Section: Discussioncontrasting
confidence: 50%
“…In the Framingham Heart Study [41], every 5-mm increase in LAD increased the development of AF by 39%. A recent study correlated rs6632677 with left ventricular remodeling [42], and it has been associated with AF risk in the Chinese population [43]. In contrast, we found that rs6632677 was not associated with risk of AF (see Supplementary Table 7), and the genotypes of the 3 ACE2 SNPs associated with LAE were also associated with increased AF risk (OR = 2.20–2.62).…”
Section: Discussioncontrasting
confidence: 50%
“…Meanwhile, we found that rs2074192 and rs879922 were not only non-correlated with IS but also had nothing to do with the recurrence risk of stroke [ 38 ]. Although rs6632677 was not associated with hypertension, dyslipidemia and stroke, it was found to be related to left ventricular remodeling [ 39 ] and possible atrial fibrillation risk in Chinese population [ 40 ]. However, association of SNP rs2048683 with hypertension, dyslipidemia and stroke had been pretty “silent”, suggesting that the loci were not protective factors but they are at least not a harmful factor on EH and EH related cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…Although this report found no connections of coexisting trabeculations that fit within NC/C ratio criteria in DCM with clinical points, it only could be partially compared to the present study and our previous study due to using triple criteria of thinning of the compact myocardium, NC/C ratio, and sufficient share of non-compact myocardium in total mass of the left ventricle [ 27 ]. The second most common combination, DCM/HCM, was found in nearly one-third of our overlapping patients, but this combination could be even more powerfully connected with undesirable prognosis due to partially shared gene basics [ 28 , 29 ]. The least frequent combination in our settings was the DCM/HCM/LVNC, with only a single case in the monitored period, which was also previously described in a large registry with clinical endpoints, which reported a greater incidence of cardiovascular adverse events [ 30 ].…”
Section: Discussionmentioning
confidence: 99%